The Application Of Experiential Learning Model Perspective David A. Kolb To Improving Students Reading Skill l Tatbiq Namudz al-Ta’alum al-Tajribi ‘inda David A. Kolb li Tarqiyyah Maharah al-Qira’ah lada Talabah - Syaifullah, Muhammad; Harun, Ubay; Izzah, Nailul; Munawar, Endang; Roji, Fatkhur; Arifin, Zaenal (Universitas Islam Negeri Raden Intan Lampung, 2021)
Reading skill is one of main skills in Arabic learning. The problems of learning in Arabic Language Education Study Program in Islamic Institute of Ma’arif NU Metro Lampung isthe method and its use in teaching the skill of reading.It is still taught in grammar translation method and direct method, which were categorized as traditional approach and method.This study aimed to measure the effectiveness of reading skill material based on experiential learning model to improve the students' reading comprehension. Quantitative research was used in this research. This research emphasized on the result of students' abilities from the specific and field experience, and conducting the pretest and post test.The objectives of this researchwas to measure the effectiveness reading skill material based on Experiential Learning model in improving the reading comprehension with 25 participants from students. The results was found thatthe reading material which is developed based on experiental learning model has given significant influence for the improvement in reading skill of student, it could be seen from the reading study result improvement of Arabic Language Education in Islamic Instituteof Ma’arif NU Metro Lampung. This research found thatExperiential Learninghas the significant impact to improve basic reading skill of students.